Limitations and potential of immunotherapy in ovarian cancer - Kumar, Sandeep; Acharya, Sayanti; Karthikeyan, Mahalakshmi; Biswas, Priyobrata; Kumari, Sudha (Frontiers in Immunology, 2024)
Ovarian cancer (OC) is the third most common gynecological cancer and alone has an emergence rate of approximately 308,069 cases worldwide (2020) with dire survival rates. To put it into perspective, the mortality rate of OC is three times higher than that of breast cancer and it is predicted to only increase significantly by 2040. The primary reasons for such a high rate are that the physical symptoms of OC are detectable only during the advanced phase of the disease when resistance to chemotherapies is high and around 80% of the patients that do indeed respond to chemotherapy initially, show a poor prognosis subsequently. This highlights a pressing need to develop new and effective therapies to tackle advanced OC to improve prognosis and patient survival. A major advance in this direction is the emergence of combination immunotherapeutic methods to boost CD8+ T cell function to tackle OC. In this perspective, we discuss our view of the current state of some of the combination immunotherapies in the treatment of advanced OC, their limitations, and potential approaches toward a safer and more effective response.